Islamic Revival in Kazakhstan from the Historical Perspective (1991-2020) - Sadvokassov, Shakhkarim; Zhumashev, Rymbek (Journal of Al-Tamaddun, 2023)
In recent years, researchers have increasingly posed the question of the role of Islam in shaping an individual’s personality, their spiritual worldview, and socio-cultural identity in the post-Soviet space. This study aims to analyze the process of Islam’s resurgence in the Republic of Kazakhstan, particularly in the context of its independence. The study employs a methodological framework grounded in the historical method of comparison. The findings underscore that Islam has evolved into an integral component of contemporary global civilization. In the era of globalization, it has undergone transformations across various levels of public life, serving as a unifying force for diverse reformist ideologies within the Islamic world. The study’s conclusion highlights the contemporary period in the Republic of Kazakhstan as characterized by a national revival. This revival encompasses the revitalization of national culture and religion, with a strong emphasis on the development of national culture rooted in traditional spiritual values. Additionally, it recognizes the significant role of religion in shaping national identity. However, it is essential to acknowledge the ongoing tension between historically entrenched aspects of Islam and modern trends. This tension underscores the Islamic resurgence as a unifying force driving reformist ideas within the Islamic world. In summary, the Republic of Kazakhstan’s modern era is marked by a profound national revival that encompasses cultural revitalization and a renewed recognition of religion’s role in shaping national identity. This revival exists alongside the ongoing interplay between historical Islamic elements and contemporary influences.